Síntese de novos derivados triazólicos e avaliação de suas atividades antifúngicas - Luciana Pereira Silva (2019)
In the last three decades, the mortality rate caused by fungal infections has substantially increased due the appearance of new pathogenic fungi and the emergence of infections resistant to the available drugs for treatment. This scenario has made the search and development of new antifungal drugs extremally relevant. In this context, this work presents the synthesis and evaluation of their activities of nine unprecedented triazole derivatives. The new molecules were design using the molecular simplification technique, in which the ravuconazole antifungal was used as the prototype substance. The new compounds were synthetized in a maximum of six steps and were characterized by infrared spectroscopy and Nuclear Magnetic Ressonance (NMR) spectroscopy of 1H, 13C and DEPT 135. Some intermediate compounds of the synthetic route were also characterized by two dimensions NMR experiments (COSY, HSQC and HMBC) to confirm their structures. The antifungal activity was evaluated by minimum inhibitory concentration tests and the fungi species tested were Candida albicans, Candida glabrata, Cryptococcus neoformans, Cryptococcus gattii, Trichophyton rubrum and Trichophyton interdigitale. For the evaluated species, the new triazole compounds were not active in an ideal concentration. However, few species were tested and further studies should be done to investigate a possible activity of the compounds synthetized in this work.